Does the Gut Microbiome Play a Role in Obesity in Type 1 Diabetes? Unanswered Questions and Review of the Literature - Ismail, Heba M.; Evans-Molina, Carmella (Frontiers in Cellular and Infection Microbiology, 2022)
Evidence suggests that type 1 diabetes (T1D) risk and progression are associated with gut bacterial imbalances. Children with either T1D or islet antibody positivity exhibit gut dysbiosis (microbial imbalance) characterized by lower gram-positive to gram-negative gut bacterial ratios compared to healthy individuals, leading to a pro-inflammatory milieu. In addition, specific gut microbiome changes, including increased virulence factors, elevated phage, prophage, and motility genes, and higher amplitude stress responses, have been identified in individuals who have or are progressing towards T1D. Additionally, gut microbiome differences are associated with and thought to contribute to obesity, a comorbidity that is increasingly prevalent among persons with T1D. Obesity in T1D is problematic because individuals with obesity progress faster to T1D, have reduced insulin sensitivity compared to their lean counterparts, and have higher risk of complications. Animal and human studies suggest higher relative abundance of bacterial taxa associated with changes in bile acid and short chain fatty acid biosynthesis in obesity. However, it is unknown to what extent the gut microbiome plays a role in obesity in T1D and these worse outcomes. In this review, we aim to evaluate potential gut microbiome changes and associations in individuals with T1D who are obese, highlighting the specific gut microbiome changes associated with obesity and with T1D development. We will identify commonalities and differences in microbiome changes and examine potential microbiota-host interactions and the metabolic pathways involved. Finally, we will explore interventions that may be of benefit to this population, in order to modify disease and improve outcomes.